2013
DOI: 10.5399/osu/jtrf.52.3.4183
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to School Bus Crashes

Abstract: School bus safety is a community concern because parents expect their children to be transported to and from school safely. However, relatively few studies have been devoted to examining the factors contributing to school bus crashes. In this study, a logistic regression model is used to delineate the factors that contribute to school bus collisions from collisions involving other types of buses. As expected, we find significant differences in crash factors arising from differences in exposure and operating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
3
8
1
Order By: Relevance
“…However, the literature on school bus related crashes is limited. We found only five school bus crash related studies [12,16,[19][20][21]. Whereas these studies have attempted to identify risk factors associated with school bus safety (e.g., [19,20]), the authors of this current study hypothesize that the contributing factors vary by the driver deemed to be at fault, i.e., the driver of the at-fault school bus and that of other vehicle that collides with the school bus.…”
Section: Research Motivationmentioning
confidence: 85%
See 2 more Smart Citations
“…However, the literature on school bus related crashes is limited. We found only five school bus crash related studies [12,16,[19][20][21]. Whereas these studies have attempted to identify risk factors associated with school bus safety (e.g., [19,20]), the authors of this current study hypothesize that the contributing factors vary by the driver deemed to be at fault, i.e., the driver of the at-fault school bus and that of other vehicle that collides with the school bus.…”
Section: Research Motivationmentioning
confidence: 85%
“…Despite the criticality of the school bus safety issue, few studies were found in the existing body of literature that directly addressed the problem [12,16,[19][20][21]. Kaplan and Prato [16] studied the risk factors associated with bus accident severity in general but considered the school bus as one of the bus service types.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, around 1.7 million students in Iran used ST [4]. Parents expect their children to go to school and return to home in safety [5] and ST can be an appropriate route for safe student transportation [6]. Nonetheless, ST carries different risks for students, increases their vulnerability [1], and creates heavy socioeconomic burden [7].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of ST crashes in Iran [16], the importance of protecting students' physical and mental health [2]. The significant role of ST drivers in protecting student health [5], and the significant effects of ST drivers' behaviors on ST crashes [8] and on student behaviors [8], quality education about safe driving and safe ST for ST drivers is necessary to improve their driving behaviors [2,17]. A key step to educational programs for ST drivers is to study their driving behaviors and their contributing factors.…”
Section: Introductionmentioning
confidence: 99%